Free-to-air football: The role of GOL TV. Analysis of the audience data and the main causes. Season 2017/18 - Berciano Jiménez, Daniel (Documentación de las Ciencias de la Información, 2020)
Private television companies have taken control of the sports world, specially the main one: football. Since some seasons ago, GOL TV is the only free-to-air channel that broadcasts first division matches, even though any team that takes part in European competitions can’t participate in these games. The social mass of the clubs, the performance of the teams and the calendar variables show up as the main factors that determinate the audience of the matches. Through this references, the study was carried out to identify the main causes that make the viewers’ figures of the games broadcasted during the season 2017/2018.